2020
DOI: 10.1109/tpel.2020.2990370
|View full text |Cite
|
Sign up to set email alerts
|

$C_{\text{oss}}$ Loss Tangent of Field-Effect Transistors: Generalizing High-Frequency Soft-Switching Losses

Abstract: The dissipated energy (E diss) related to the resonant charging/discharging of a transistor output capacitance, becomes a dominant loss factor for power converters operating in the MHz range. A recent work has introduced a small-signal measurement method to quantify E diss with a frequency-dependent small-signal resistance, Rs, and an effective small-signal output capacitance, C eff oss. This work provides further insights on the effect of Rs and Coss upon the device losses in a broader sense. In particular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The displacement loss is mainly taken place due to voltage swings across the blocking substrate when the device is kept OFF. For the currently available and popular devices such as GaN-HEMT, there is unexpected extra losses associated to the 𝐶 𝑂𝑆𝑆 which contributes to additional power losses on the device [55] [56]. This loss cannot be mitigated with any external circuit operations but is intrinsic to the device materials.…”
Section: A Power Losses Versus Operating Frequency For Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement loss is mainly taken place due to voltage swings across the blocking substrate when the device is kept OFF. For the currently available and popular devices such as GaN-HEMT, there is unexpected extra losses associated to the 𝐶 𝑂𝑆𝑆 which contributes to additional power losses on the device [55] [56]. This loss cannot be mitigated with any external circuit operations but is intrinsic to the device materials.…”
Section: A Power Losses Versus Operating Frequency For Powermentioning
confidence: 99%
“…But it is uncertain if device manufacturers would adopt such techniques at the expense of other aspects of device performance and costs. Reference [56] indicates that the loss tangent (𝛿) is constant to the device family and can be used as a figure-of-merit for selecting switching devices. Such loss also applies to capacitors connected in shunt to the switches, such as the multi-layer ceramic capacitors (MLCC) used for adjusting ZVS quasi-resonant times.…”
Section: A Power Losses Versus Operating Frequency For Powermentioning
confidence: 99%
“…However, it has been reported that in the LLC (and other resonant converters), although the high-voltage (HV) primary side devices are soft-switched, their switching loss does not completely disappear [8]. The phenomenon can be interpreted as an equivalent series resistance (R oss ) appearing in series to the output capacitance of the devices (C oss ) during the resonant transitions [9][10][11][12][13][14][15][16]. However, there are no similar reports about the soft-switching loss contribution of the secondary side low-voltage (LV) rectifiers, even though the most mature technology for the LV secondary side rectifiers is the Silicon (Si) Trench MOSFET with shield-plate [17][18][19][20][21], and it is known that in their construction a series resistance appears with the output capacitance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However the paper presents only a quantitative analysis of the output capacitance loss. The work in [40] further investigates this phenomenon and presents that dissipated energy is the result of dielectric loss in the output capacitance. This can be modeled as a frequency dependent resistance in series with the output capacitor shown in Fig.…”
Section: Output Capacitance (C Oss ) Lossmentioning
confidence: 99%
“…The frequency dependent resistance is small-signal measurement using the impedance analyzer while the frequency is swept from 100 kHz -100 MHz. According to the paper [40], the dissipation loss in the output capacitance due to this series resistance is calculated as (2.13).…”
Section: Output Capacitance (C Oss ) Lossmentioning
confidence: 99%